2015
DOI: 10.1186/s12883-015-0370-9
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and concurrence of anxiety and depression among attendees with multiple sclerosis at a tertiary care Hospital in Oman

Abstract: BackgroundAnxiety, depression and functional impairments are commonly reported by persons with multiple sclerosis (PwMS) but no data, to our knowledge, has emerged from an Arab Islamic population. The study aims to investigate the prevalence of anxiety, depression and related disabilities among PwMS attending tertiary care in Sultan Qaboos University Hospital (SQUH), one of the urban hospitals in Oman.MethodsConsecutive and consenting PwMS (n = 57) and healthy subjects (n = 53) completed the following measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 55 publications
0
9
1
Order By: Relevance
“…Only one pilot study has been conducted on the link between depression and MS in the UAE. 15 However, that study did not find an increased rate of depression, unlike several studies in other Arab countries, 15,16 possibly due to the small sample size and single-center nature of the study. The present study aimed to examine these findings in a multicenter study with a larger sample size and explore the differences in depression as a function of demographic variables and disease characteristics.…”
Section: Patient Characteristicscontrasting
confidence: 74%
“…Only one pilot study has been conducted on the link between depression and MS in the UAE. 15 However, that study did not find an increased rate of depression, unlike several studies in other Arab countries, 15,16 possibly due to the small sample size and single-center nature of the study. The present study aimed to examine these findings in a multicenter study with a larger sample size and explore the differences in depression as a function of demographic variables and disease characteristics.…”
Section: Patient Characteristicscontrasting
confidence: 74%
“…Most of the studies were cohort studies without control subjects and overall, global prevalence rates for depression and anxiety ranged from 21.1-59.4% to 28.1-57.0% for depression and anxiety, respectively. Several studies reported depression at ~ 35% [40][41][42][43][44][45][46][47][48][49] and anxiety at ~ 55% in PwMS [43][44][45][46][49][50][51][52], and exceptionally low rates were observed for studies performed in Abu Dhabi (10.8-17.5% for depression and 4.8-20.0% for anxiety) [53,54]. Jun-O'Connell et al reported an increased prevalence of bipolar disorder in PwMS in a cohort from the US (type 1 was more significantly more prevalent than type 2 in the study group: 60% versus 30%, respectively), although this study lacked a control group.…”
Section: Depression Anxiety and Bipolar Disorder (Supplementalmentioning
confidence: 99%
“…There is evidence to suggest a tendency to lean towards a 'collective' social orientation, which is in contrast to 'individualistic' social orientation commonly found in Western countries. To preserve social harmony, according to Al Asmi et al [ 43 ], "such a society tends to discourage the expression of emotion and therefore relegates emotional distress. Instead, distress is expressed in somatic terms, a feat that is orthogonal to what may constitute emotional distress in the psychiatric nomenclature…" (p.6).…”
Section: Discussionmentioning
confidence: 99%